2017
DOI: 10.1002/eap.1437
|View full text |Cite
|
Sign up to set email alerts
|

Sound settlement: noise surpasses land cover in explaining breeding habitat selection of secondary cavity‐nesting birds

Abstract: Birds breeding in heterogeneous landscapes select nest sites by cueing in on a variety of factors from landscape features and social information to the presence of natural enemies. We focus on determining the relative impact of anthropogenic noise on nest site occupancy, compared to amount of forest cover, which is known to strongly influence the selection process. We examine chronic, industrial noise from natural gas wells directly measured at the nest box as well as site-averaged noise, using a well-establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 60 publications
1
23
2
Order By: Relevance
“…In combination with raised vigilance levels in noisy conditions (Quinn et al, 2006;Chan et al, 2010), this may further impact fitness prospects in noisy areas. Hence, avoiding noisy areas (given a choice) might well be beneficial for the birds and is in line with observed distribution patterns in the field in different songbird species (Parris & Schneider, 2009;Arévalo & Newhard, 2011;Goodwin & Shriver, 2011;Herrera-Montes & Aide, 2011;Proppe et al, 2013) and with avoidance patterns of (experimentally induced) noisy nest boxes (Kleist et al, 2017;Injaian et al, 2018a) or stopover sites near an experimental 'phantom road ' (McClure et al, 2013).…”
Section: Recording Distance Dependent Response Patternsupporting
confidence: 74%
“…In combination with raised vigilance levels in noisy conditions (Quinn et al, 2006;Chan et al, 2010), this may further impact fitness prospects in noisy areas. Hence, avoiding noisy areas (given a choice) might well be beneficial for the birds and is in line with observed distribution patterns in the field in different songbird species (Parris & Schneider, 2009;Arévalo & Newhard, 2011;Goodwin & Shriver, 2011;Herrera-Montes & Aide, 2011;Proppe et al, 2013) and with avoidance patterns of (experimentally induced) noisy nest boxes (Kleist et al, 2017;Injaian et al, 2018a) or stopover sites near an experimental 'phantom road ' (McClure et al, 2013).…”
Section: Recording Distance Dependent Response Patternsupporting
confidence: 74%
“…If noise reduces foraging intake rates then we would expect animals to spend more time in quiet areas than noisy ones. Animals have been shown to avoid noisy areas when making breeding habitat decisions [36, 37], but few studies exist examining how noise affects choice of foraging location (but see: [6, 20, 3840]).…”
Section: Introductionmentioning
confidence: 99%
“…type. Yet recent work found that variation in the acoustic environment better explained breeding distributions of two species than did gradients in vegetation 19 , emphasizing the benefits of examining existing dogma with a sensory lens. Reimagining conservation to include sensory perspectives conveys pragmatic benefits.…”
Section: Main Textmentioning
confidence: 99%